The 15th international workshop on modeling the ocean (IWMO-2025) in Stanford, California, USA, June 30th – July 1st, 2025 - Oliver Fringer; Ricardo de Camargo; Yu-Lin Chang; Huijie Xue; Tal Ezer (Ocean Dynamics, 2026)

The 14th International Workshop on Modeling the Ocean (IWMO-2024) in Sapporo, Japan, 17–20 June 2024 - Yutaka Yoshikawa; Joanna Staneva; Joseph Zhang; Yu-Lin Chang; Amin Chabchoub; Tal Ezer (Ocean Dynamics, 2026)

On the contribution of the Gulf stream to high frequency coastal sea level variability - Tal Ezer (Ocean Dynamics, 2026)
Long-term Atlantic Ocean and Gulf Stream (GS) variability were linked in past studies to coastal sea level (CSL) change along the U.S. East Coast – a weakening GS can lead to rise in CSL and increased coastal flooding. However, high frequency variability (HFV) in CSL is, in most cases, attributed to atmospheric weather events. This study is focused on HFV (intraseasonal variations with periods between ~ 1 week and ~ 2 months) in the GS and in CSL. First, wavelet and spectral analysis of observations of the Florida Current transport and CSL characterized the HFV in the data, and then idealized numerical simulations were conducted to study the response of CSL to imposed GS variations with known frequencies. Three experiments were conducted: a control run with constant surface and boundary forcing, and two experiments with imposed oscillations in the Florida Current transport into the model domain- a “high-frequency experiment” (HFE) and a “low-frequency experiment” (LFE), where the period of the GS oscillations were ~ 1–2 weeks and ~ 1–2 months, respectively. The observations and the model show statistically significant anticorrelation between the GS flow and the CSL, but the LFE resulted in higher GS-CSL correlations and was more like the observations than the HFE was. The results also show large spatial differences in the CSL response to GS variations - the South-Atlantic Bight (SAB) responded more strongly to the LFE while the Mid-Atlantic Bight (MAB) responded more strongly to the HFE. Power spectra of the model simulations show that even small, imposed GS oscillations at high frequency, can interact with natural variability to excite unpredictable CSL variabilities over a wide range of frequencies, including oscillations at much longer time scales than the forcing. The variability in the Florida Current flow generated a northward propagating signal along the GS path and a southward propagating sea level signal along the coast. However, the topography near Cape Hatteras seems to partly block communication between the MAB and the SAB. The study demonstrates the important contribution of high frequency GS variability to CSL variability - better understanding of the role of remote forcing on coastal sea level can help to improve prediction of coastal sea level variations and associated flooding.

Ocean dynamics in 2025: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Diego Bruciaferri; Sandro Carniel; Amin Chabchoub; W. Bryce Corlett; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Tsubasa Kodaira; et al. (Ocean Dynamics, 2026)

The coastal ocean and shelf seas task team (COSS-TT) meeting, Montreal, Canada, May 2–4, 2023 - Tal Ezer; Alexander Kurapov; Mauro Cirano; Tomasz Dabrowski; Cristina Forbes; Pierre De Mey-Frémaux; Vassiliki Kourafalou (Ocean Dynamics, 2025)

The 13th international workshop on modeling the ocean (IWMO) in Hamburg, Germany, 27–30 June 2023 - Joanna Staneva; Tal Ezer; Jia Wang; Ricardo de Camargo; Oliver Fringer (Ocean Dynamics, 2025)

Surface currents in the Mid-Atlantic Bight: the role of the Gulf Stream versus wind - Tal Ezer (Frontiers in Marine Science, 2025)
Surface currents of the Mid-Atlantic Bight (MAB) were studied using high-frequency radar (HFR) observations at 6 km resolution during a 5-year period (2020–2024). The study’s focus on the role of the Gulf Stream (GS) contrasts with most past studies that focused on the seasonal wind-driven currents. Empirical orthogonal function (EOF) analyses of the daily HFR currents were conducted with and without the GS, revealing modes of current variability linked to the seasonal wind pattern and storms versus modes linked to GS variability. The remote impact of the GS on coastal currents is complex, with different impacts seen on different parts of the MAB. For example, unusual GS meanders that move close to the coast impact flow variability near the shelf-break front, while other locations may be influenced by the strength of the GS and shift in the mean position of the GS. In general, it was found that monthly wind may be responsible for approximately 50%–80% of the surface current variability over the entire MAB, while the GS position and speed are correlated with the offshore component of the coastal currents and linked to approximately 10%–30% of the current variability. There are also large interannual variations, so that during some years, the GS impact on the coast is larger than during other years. Comparison between geostrophic velocity derived from altimeter data and the HFR surface currents shows the influence of the GS path on the offshore currents; however, close to the coast, the currents are wind- and river-driven, so that geostrophic currents obtained from altimeter data are not reliable. Therefore, combining altimeter and HFR data will provide a better current field than each data set alone. The study demonstrates the usefulness of the HFR data to study coastal dynamics and links between the coast and open ocean variability.

Editorial– Ocean dynamics in 2024: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Sandro Carniel; Chabchoub Amin; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Pierre F. J. Lermusiaux; Zhiyu Liu; Yasumasa Miyazawa; et al. (Ocean Dynamics, 2025)

Comparing surface currents near the mouth of three bays along the U.S. East Coast: Chesapeake Bay, Delaware Bay, and New York Bay - Tal Ezer; Teresa Updyke (Ocean Dynamics, 2025)
Monthly surface currents at 2 km resolution near the mouths of three U.S. east coast bays were obtained from high-frequency radars (Coastal Ocean Dynamics Application Radar, CODAR) during 2012–2024. The currents near these bays, the Chesapeake Bay (CB), the Delaware Bay (DB) and the New York Bay (NB) were analyzed to infer similarity and differences, as well as potential common forcing from regional and basin-scale factors. The contribution to flow variability from local and remote forcing is evaluated by comparing surface currents with (a) river discharges into each bay, (b) with local and regional winds, and (c) with the North Atlantic Oscillation (NAO). The results show that surface flow variability near the mouth of the bays is linked with all three driving factors. The three bays often show similar flow patterns not only of the seasonal cycle, but also during extreme weather events. For example, increased surface flow into the bays from the Atlantic Ocean is seen when hurricanes are observed offshore in the fall, and increased surface flow from the bays is seen during winter storms. During positive NAO phases, eastward flow from all three bays increased due to intensified westerly winds, while during negative NAO phases flow decreased with weakening winds in the region. River discharges into the bays increased during 2012–2019 but decreased during 2019–2024. This change in river discharge trend was especially large in the CB, resulting in a change in trends of the surface currents. Monthly currents of each bay are only weakly correlated with the monthly river flow ( R ~ 0.2–0.3; P < 0.05), while the seasonal cycles of rivers and currents have higher correlations ( R ~ 0.6–0.7). Local winds show high correlations with the monthly currents ( R ~ 0.75) with the current direction ~ 45° to the right of the wind, as expected from Ekman theory. However, contributions to current variability from regional and remote factors cannot be ignored. The results demonstrate the complex nature of the currents near the mouth of bays since multiple drivers, including estuarine, coastal and open ocean dynamics contribute to the observed variability.

On the links between sea level and temperature variations in the Chesapeake Bay and the Atlantic Meridional Overturning Circulation (AMOC) - Tal Ezer; Teresa Updyke (Ocean Dynamics, 2024)
Recent studies found that on long time scales there are often unexplained opposite trends in sea level variability between the upper and lower Chesapeake Bay (CB). Therefore, daily sea level and temperature records were analyzed in two locations, Norfolk in the southern CB and Baltimore in the northern CB; surface currents from Coastal Ocean Dynamics Application Radar (CODAR) near the mouth of CB were also analyzed to examine connections between the CB and the Atlantic Ocean. The observations in the bay were compared with daily Atlantic Meridional Overturning Circulation (AMOC) observations during 2005–2021. Empirical Mode Decomposition (EMD) analysis was used to show that variations of sea level and temperature in the upper and lower CB are positively correlated with each other for short time scales of months to few years, but anticorrelated on low frequency modes representing decadal variability and long-term nonlinear trends. The long-term CB modes seem to be linked with AMOC variability through variations in the Gulf Stream and the wind-driven Ekman transports over the North Atlantic Ocean. AMOC variability correlates more strongly with variability in the southern CB near the mouth of the bay, where surface currents indicate potential links with AMOC variability. For example, when AMOC and the Gulf Stream were especially weak during 2009–2010, sea level in the southern bay was abnormally high, temperatures were colder than normal and outflow through the mouth of CB was especially high. Sea level in the upper bay responded to this change only 1–2 years later, which partly explains phase differences within the bay. A persistent trend of 0.22 cm/s per year of increased outflow from the CB, may be a sign of a climate-related trend associated with combination of weakening AMOC and increased precipitation and river discharge into the CB.

Editorial – Ocean Dynamics in 2023: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Sandro Carniel; Chabchoub Amin; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Richard J. Greatbatch; Pierre F. J. Lermusiaux; Zhiyu Liu; et al. (Ocean Dynamics, 2024)

The 12th International Workshop on Modeling the Ocean (IWMO 2022) in Ann Arbor, Michigan, USA on June 28–July 1, 2022 - Jia Wang; Tal Ezer; Ricardo de Camargo; Yasumasa Miyazawa; Joanna Staneva; Fanghua Xu (Ocean Dynamics, 2024)

In memoriam: Prof. Dr. Jörg-Olaf Wolff (1959–2023) - Tal Ezer (Ocean Dynamics, 2023)

Evaluation of the applicability of the Ekman theory for wind-driven ocean currents: a comparison with the Mellor–Yamada turbulent model - Tal Ezer (Ocean Dynamics, 2023)

Sea level acceleration and variability in the Chesapeake Bay: past trends, future projections, and spatial variations within the Bay - Tal Ezer (Ocean Dynamics, 2023)

Thank you to 2022 Ocean Dynamics reviewers - Tal Ezer; Sandro Carniel; Chabchoub Amin; Ricardo de Camargo; Sheila N. Estrada-Allis; Guoping Gao; Richard J. Greatbatch; Pierre F. J. Lermusiaux; Zhiyu Liu; Yasumasa Miyazawa; Alejandro Orfila Forster; Swapna Panickal; et al. (Ocean Dynamics, 2023)

Sea level variability in the Gulf of Mexico since 1900 and its link to the Yucatan Channel and the Florida Strait flows - Tal Ezer (Ocean Dynamics, 2022)

The impact of remote temperature anomalies on the strength and position of the Gulf Stream and on coastal sea level variability: a model sensitivity study - Tal Ezer; Sönke Dangendorf (Ocean Dynamics, 2022)

Spatiotemporal variability of the ocean since 1900: testing a new analysis approach using global sea level reconstruction - Tal Ezer; Sönke Dangendorf (Ocean Dynamics, 2022)

Variability and upward trend in the kinetic energy of western boundary currents over the last century: impacts from barystatic and dynamic sea level change - Tal Ezer; Sönke Dangendorf (Climate Dynamics, 2021)

The 11th International Workshop on Modeling the Ocean (IWMO 2019) in Wuxi, China, on June 17–20, 2019 - Tal Ezer; Fanghua Xu; Zhiyu Liu; Emil Stanev; Shanlin Wang; Jun Wei (Ocean Dynamics, 2021)

Global sea level reconstruction for 1900–2015 reveals regional variability in ocean dynamics and an unprecedented long weakening in the Gulf Stream flow since the 1990s - Tal Ezer; Sönke Dangendorf (Ocean Science, 2020)
A new monthly global sea level reconstruction for 1900–2015 was analyzed and compared with various observations to examine regional variability and trends in the ocean dynamics of the western North Atlantic Ocean and the US East Coast. Proxies of the Gulf Stream (GS) strength in the Mid-Atlantic Bight (GS-MAB) and in the South Atlantic Bight (GS-SAB) were derived from sea level differences across the GS. While decadal oscillations dominate the 116-year record, the analysis showed an unprecedented long period of weakening in the GS flow since the late 1990s. The only other period of long weakening in the record was during the 1960s–1970s, and red noise experiments showed that is very unlikely that those just occurred by chance. Ensemble empirical mode decomposition (EEMD) was used to separate oscillations at different timescales, showing that the low-frequency variability of the GS is connected to the Atlantic Multi-decadal Oscillation (AMO) and the Atlantic Meridional Overturning Circulation (AMOC). The recent weakening of the reconstructed GS-MAB was mostly influenced by weakening of the upper mid-ocean transport component of AMOC as observed by the RAPID measurements for 2005–2015. Comparison between the reconstructed sea level near the coast and tide gauge data for 1927–2015 showed that the reconstruction underestimated observed coastal sea level variability for timescales less than ∼5 years, but lower-frequency variability of coastal sea level was captured very well in both amplitude and phase by the reconstruction. Comparison between the GS-SAB proxy and the observed Florida Current transport for 1982–2015 also showed significant correlations for oscillations with periods longer than ∼5 years. The study demonstrated that despite the coarse horizontal resolution of the global reconstruction (1∘ × 1∘), long-term variations in regional dynamics can be captured quite well, thus making the data useful for studies of long-term variability in other regions as well.

The 10th International Workshop on Modeling the Ocean (IWMO 2018) in Santos, Brazil, June 25–28, 2018 - Tal Ezer; Ricardo de Camargo; Clemente A. S. Tanajura; Fanghua Xu; Huijie Xue (Ocean Dynamics, 2020)

Analysis of the changing patterns of seasonal flooding along the U.S. East Coast - Tal Ezer (Ocean Dynamics, 2020)

The 9th International Workshop on Modeling the Ocean (IWMO 2017) in Seoul, Korea, July 3–6, 2017 - Lie-Yauw Oey; Yign Noh; Jarle Berntsen; Sung Yong Kim; Humio Mitsudera; Tal Ezer (Ocean Dynamics, 2020)

Impacts of Basin-Scale Climate Modes on Coastal Sea Level: a Review - Weiqing Han; Detlef Stammer; Philip Thompson; Tal Ezer; Hindu Palanisamy; Xuebin Zhang; Catia M. Domingues; Lei Zhang; Dongliang Yuan (Surveys in Geophysics, 2019)

Numerical modeling of the impact of hurricanes on ocean dynamics: sensitivity of the Gulf Stream response to storm’s track - Tal Ezer (Ocean Dynamics, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

On the interaction between a hurricane, the Gulf Stream and coastal sea level - Tal Ezer (Ocean Dynamics, 2018)

Description and Mechanisms of the Mid-Year Upwelling in the Southern Caribbean Sea from Remote Sensing and Local Data - Digna Rueda-Roa; Tal Ezer; Frank Muller-Karger (Journal of Marine Science and Engineering, 2018)
The southern Caribbean Sea experiences strong coastal upwelling between December and April due to the seasonal strengthening of the trade winds. A second upwelling was recently detected in the southeastern Caribbean during June–August, when local coastal wind intensities weaken. Using synoptic satellite measurements and in situ data, this mid-year upwelling was characterized in terms of surface and subsurface temperature structures, and its mechanisms were explored. The mid-year upwelling lasts 6–9 weeks with satellite sea surface temperature (SST) ~1–2° C warmer than the primary upwelling. Three possible upwelling mechanisms were analyzed: cross-shore Ekman transport (csET) due to alongshore winds, wind curl (Ekman pumping/suction) due to wind spatial gradients, and dynamic uplift caused by variations in the strength/position of the Caribbean Current. These parameters were derived from satellite wind and altimeter observations. The principal and the mid-year upwelling were driven primarily by csET (78–86%). However, SST had similar or better correlations with the Ekman pumping/suction integrated up to 100 km offshore (WE100) than with csET, possibly due to its influence on the isopycnal depth of the source waters for the coastal upwelling. The mid-year upwelling was not caused by dynamic uplift but it might have been enhanced by the seasonal intensification of the Caribbean Current during that period.

Editorial—the 8th International Workshop on Modeling the Ocean (IWMO 2016) in Bologna, Italy, June 7–10, 2016 - Tal Ezer; Lie-Yauw Oey; Huijie Xue; Marco Zavatarelli; Gianmaria Sannino; Ricardo de Camargo (Ocean Dynamics, 2018)

Editorial—the 7th International Workshop on Modeling the Ocean (IWMO 2015) - Lie-Yauw Oey; Xiao Hua Wang; Tal Ezer; Yign Noh; Andrew McC. Hogg (Ocean Dynamics, 2017)

On the predictability of high water level along the US East Coast: can the Florida Current measurement be an indicator for flooding caused by remote forcing? - Tal Ezer; Larry P. Atkinson (Ocean Dynamics, 2017)

A modeling study of the role that bottom topography plays in Gulf Stream dynamics and in influencing the tilt of mean sea level along the US East Coast - Tal Ezer (Ocean Dynamics, 2017)

Editorial—The 6th International Workshop on Modeling the Ocean (IWMO 2014) - Lie-Yauw Oey; Tal Ezer; Jinyu Sheng; Fei Chai; Jianping Gan; Kevin Lamb; Yasumasa Miyazawa (Ocean Dynamics, 2017)

Fish spawning aggregations: where well‐placed management actions can yield big benefits for fisheries and conservation - Brad Erisman; William Heyman; Shinichi Kobara; Tal Ezer; Simon Pittman; Octavio Aburto‐Oropeza; Richard S Nemeth (Fish and Fisheries, 2017)
Marine ecosystem management has traditionally been divided between fisheries management and biodiversity conservation approaches, and the merging of these disparate agendas has proven difficult. Here, we offer a pathway that can unite fishers, scientists, resource managers and conservationists towards a single vision for some areas of the ocean where small investments in management can offer disproportionately large benefits to fisheries and biodiversity conservation. Specifically, we provide a series of evidenced‐based arguments that support an urgent need to recognize fish spawning aggregations ( FSA s) as a focal point for fisheries management and conservation on a global scale, with a particular emphasis placed on the protection of multispecies FSA sites. We illustrate that these sites serve as productivity hotspots – small areas of the ocean that are dictated by the interactions between physical forces and geomorphology, attract multiple species to reproduce in large numbers and support food web dynamics, ecosystem health and robust fisheries. FSA s are comparable in vulnerability, importance and magnificence to breeding aggregations of seabirds, sea turtles and whales yet they receive insufficient attention and are declining worldwide. Numerous case‐studies confirm that protected aggregations do recover to benefit fisheries through increases in fish biomass, catch rates and larval recruitment at fished sites. The small size and spatio‐temporal predictability of FSA s allow monitoring, assessment and enforcement to be scaled down while benefits of protection scale up to entire populations. Fishers intuitively understand the linkages between protecting FSA s and healthy fisheries and thus tend to support their protection.

Can the Gulf Stream induce coherent short-term fluctuations in sea level along the US East Coast? A modeling study - Tal Ezer (Ocean Dynamics, 2016)

Editorial—the 5th International workshop on modeling the ocean (IWMO 2013) - Jarle Berntsen; Lie-Yauw Oey; Tal Ezer; Richard Greatbatch; Huijie Xue; Yasumasa Miyazawa (Ocean Dynamics, 2014)

On the dynamics of low latitude, wide and shallow coastal system: numerical simulations of the Upper Gulf of Thailand - Suriyan Saramul; Tal Ezer (Ocean Dynamics, 2014)

Editorial—the 4th International Workshop on Modeling the Ocean (IWMO 2012) - Lie-Yauw Oey; Yasumasa Miyazawa; Hidenori Aiki; Yukio Masumoto; Tal Ezer; Takuji Waseda (Ocean Dynamics, 2013)

River discharge predicts spatial distributions of beluga whales in the Upper Cook Inlet, Alaska, during early summer - Julian R. Ashford; Tal Ezer; Cynthia M. Jones (Polar Biology, 2013)

Editorial—The 3rd International Workshop on Modeling the Ocean (IWMO 2011) - Lie-Yauw Oey; Tal Ezer; Bo Qiu; Jarle Berntsen; Ruoying He (Ocean Dynamics, 2013)

On the dynamics of strait flows: an ocean model study of the Aleutian passages and the Bering Strait - Tal Ezer; Lie-Yauw Oey (Ocean Dynamics, 2013)

Extreme flows and unusual water levels near a Caribbean coral reef: was this a case of a “perfect storm”? - Tal Ezer; William D. Heyman; Chris Houser; Björn Kjerfve (Ocean Dynamics, 2012)

Editorial—The 2nd International Workshop on Modeling the Ocean (IWMO-2010) - Tal Ezer; Lie-Yauw Oey; Huijie Xue; Xiao Hua Wang (Ocean Dynamics, 2011)

Modeling and observations of high-frequency flow variability and internal waves at a Caribbean reef spawning aggregation site - Tal Ezer; William D. Heyman; Chris Houser; Björn Kjerfve (Ocean Dynamics, 2011)

Editorial—International Workshop on Modeling the Ocean (IWMO) special issue part 2 in ocean dynamics - Lie-Yauw Oey; Tal Ezer; Yasumasa Miyazawa; Chau-Ron Wu (Ocean Dynamics, 2010)

A three-dimensional surface wave–ocean circulation coupled model and its initial testing - Fangli Qiao; Yeli Yuan; Tal Ezer; Changshui Xia; Yongzeng Yang; Xingang Lü; Zhenya Song (Ocean Dynamics, 2010)

On the dynamics and morphology of extensive tidal mudflats: Integrating remote sensing data with an inundation model of Cook Inlet, Alaska - Tal Ezer; Hua Liu (Ocean Dynamics, 2010)

Editorial—International Workshop on Modeling the Ocean (IWMO) special issue in Ocean Dynamics - Lie-Yauw Oey; Tal Ezer; Yasumasa Miyazawa; Chau-Ron Wu (Ocean Dynamics, 2010)

Tidal-driven dynamics and mixing processes in a coastal ocean model with wetting and drying - Suriyan Saramul; Tal Ezer (Ocean Dynamics, 2010)

Multi-core structure of the Kuroshio in the East China Sea from long-term transect observations - Hong-Xia Chen; Fang-Li Qiao; Tal Ezer; Ye-Li Yuan; Feng Hua (Ocean Dynamics, 2009)

On the Movement of Beluga Whales in Cook Inlet, Alaska: Simulations of Tidal and Environmental Impacts Using a Hydrodynamic Inundation Model - Tal Ezer; Roderick Hobbs; Lie-Yauw Oey (Oceanography, 2008)

Baroclinic tidal flows and inundation processes in Cook Inlet, Alaska: numerical modeling and satellite observations - Lie-Yauw Oey; Tal Ezer; Chuanmin Hu; Frank E. Muller-Karger (Ocean Dynamics, 2007)

On the variability of the flow along the Meso-American Barrier Reef system: a numerical model study of the influence of the Caribbean current and eddies - Tal Ezer; Deeptha V. Thattai; Björn Kjerfve; William D. Heyman (Ocean Dynamics, 2005)